The National Osteoporosis Foundation's methods and processes for developing position statements. Issue 1 (December 2016) - Wallace, Taylor; Bauer, Douglas; Gagel, Robert; Greenspan, Susan; Lappe, Joan; LeBoff, Meryl; Recker, Robert; Saag, Kenneth; Singer, Andrea
Abstract Summary The methods and processes described in this manuscript have been approved and adopted by the NOF Board of Trustees on November 11, 2015. This manuscript has been peer-reviewed by the NOF Research Committee andOsteoporosis International . The National Osteoporosis Foundation frequently publishes position statements for the benefit of educating healthcare professionals and the general public on a particular issue and/or concern related to preventing osteoporosis and/or promoting strong bones throughout the lifespan. This manuscript represents the official methods and processes adopted by the NOF Board of Trustees for the purpose developing future position statements in a transparent and unbiased manner.